2011
DOI: 10.1016/j.jorganchem.2010.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of copper(II) as a new alkene amination promoter and catalyst

Abstract: Copper(II) carboxylates and chiral copper(II) triflate·bis(oxazoline) complexes promote and catalyze intramolecular alkene carboamination, diamination and aminooxygenation reactions, creating an array of nitrogen heterocycles. High diastereoselectivity and enantioselectivity can be achieved in these transformations. This account reviews the discovery and development of these useful and interesting reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 57 publications
(59 reference statements)
1
47
0
Order By: Relevance
“…10 The particular aminofunctionalization observed is a function of substrate structure and reaction components. 11 The reaction disclosed herein significantly extends our previously reported doubly intramolecular carboamination methodology 7 to an intermolecular C–C bond-forming process by using aryl-substituted alkenes as the otherwise unfunctionalized p -component. 12 The resulting allyl-functionalized chiral indoline, pyrrolidine, and tetrahydroisoquinoline products ( vide infra ) should find application in drug discovery and organic synthesis.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…10 The particular aminofunctionalization observed is a function of substrate structure and reaction components. 11 The reaction disclosed herein significantly extends our previously reported doubly intramolecular carboamination methodology 7 to an intermolecular C–C bond-forming process by using aryl-substituted alkenes as the otherwise unfunctionalized p -component. 12 The resulting allyl-functionalized chiral indoline, pyrrolidine, and tetrahydroisoquinoline products ( vide infra ) should find application in drug discovery and organic synthesis.…”
supporting
confidence: 66%
“…13 At the onset, we were uncertain if intermolecular radical addition to DPE would out-compete an intramolecular carboamination process, where the radical adds to the aryl ring of the tosyl group, generating sultam 3 . 7a While the reaction promoted by Cu(2-ethylhexanoate) 2 , a copper(II) source known to promote the alkene amination step, 11 provided a low yield of 2a (Table 1, entry 1), the catalytic version, using Cu(OTf) 2 (20 mol%), the 2,2′-bipyridine ligand, and MnO 2 (3 equiv) as the stoichiometric oxidant provided a higher yield of 2a (Table 1, entry 2). Encouraged by these results, we further employed ( R,R )-Ph-box as the ligand to enable an enantioselective variant.…”
mentioning
confidence: 99%
“…[10c] The fate of the carbon radical is influenced by the substrate structure and reaction components, and both determine which difunctionalized product is formed. [13] We hypothesized that if we could identify a halogen atom donor with a greater propensity for atom transfer than for electrophilic halogenation under our Cu-catalyzed reaction conditions, the enantioselective aminocupration step would be favored over non-catalyzed (racemic) background processes. An initial screen of several halogen sources (NBS, CBr 4 , NIS, I 2 , and 2,4,4,6-tetrabromocyclohexa-2,5-dienone) revealed that significant background aminohalogenation occurred under the reaction conditions in the absence of the [Cu( R , R )-Ph-box](OTf) 2 catalyst.…”
mentioning
confidence: 99%
“…Finally, this aminohalogenation is the first example of an efficient atom transfer process occurring in this class of Cu-catalyzed alkene amination reactions. [13] …”
mentioning
confidence: 99%
“…A series of impressive protocols to this end were developed by Chemler [68]. Based on a series of stoichiometric developments, Chemler could devise carboamination reactions, in which a nitrogen substituent undergoes radical C-H activation/C-C coupling.…”
Section: Other Oxygenation Reactions Involving Wacker-type Chemistry mentioning
confidence: 99%